Dosificación de lactasa en la fermentación con saccharomyces cerevisiae para la obtención de alcohol utilizando lactosuero - Arroyo Villa, Mario Enrique (2018)
The purpose of this work was to obtain alcohol from whey, for which yeast of the species Saccharomyces Cerevisiae US-05 was used; S-04 genetically modified and the enzyme called lactase. A completely randomized design (DCA) was used in bifactorial design AxB which had 2 factors under study, factor A: Types of yeast Saccharomyces Cerevisiae had 2 levels (S0-4 and US-05); Factor B: Dosage of lactase with four levels (0.25 ml, 0.50 ml, 0.75 ml, 1 ml of lactase per liter of raw material), each treatment was composed of 3 liters of whey. The raw material was analyzed for pH, acidity and brix degrees as control measures. The fermentation process lasted for 22 days, then the distillation process was carried out for each of the treatments with their respective replicas. The data obtained were analyzed by means of the statistical program IBM SPSS version 21, resulting in the variable T4 treatment (3 ml of lactase + 3 g of yeast Saccharomyces Cerevisiae US-05 + 3 L of whey) for the variable alcohol yield. more suitable, while for the variable alcohol concentration with T1 treatments (0.75 ml of lactase + 3 g of yeast Saccharomyces cerevisiae US-05 +3 L of whey) and T4 (3 ml of lactase + 3 g of yeast Saccharomyces Cerevisiae US-05 + 3 L of whey) a higher alcohol concentration was obtained.